The crystal growth, intercellular spacing and microsegregation of selective laser melted Inconel 718 superalloy. (January 2019) - Tao, Pan; Li, Huaixue; Huang, Baiying; Hu, Quandong; Gong, Shuili; Xu, Qingyan
Abstract: The solidified microstructure of SLM-fabricated IN718 was investigated from macroscopic to microscopic perspective in this study using optical microscope, scanning electron microscope, transmission electron microscopy. Based on the experimental results and theoretical analysis, the solidification behavior, the characteristics of the primary dendrite spacing λ 1 and microsegregation were elucidated. In the present SLM-produced IN718, the solidification starts at the molten pool boundaries by the epitaxial growth. The solidification rate is estimated in the range of 0.1–1 m/s. The newly-formed crystals grow into cellular dendrites, the direction of which is either parallel to the original direction or changed by 90°. The primary dendrite spacing λ1 varies over a wide range of 27.6 × 10 −2 ∼147.3 × 10 −2  μm due to dramatically changeable average cooling rate from 1.1 × 10 5 –1.2 × 10 7  °C/s. There is a significant microsegregation of Nb in the inter-dendritic region, leading to the formation of Laves phases, the amount of which is about 9.0 ± 1.3%. Meanwhile, a solute trapping of Nb in the dendritic trunk occurs during rapid solidification. Highlights: The solidification rate during SLM of IN718 was estimated to be in range of 0.1–1 m/s. The solidification mode was cellular-dendritic growth. The inter-dendritic microsegregation of Nb and Mo resulted in the formation of Laves phases. A solute trapping of Nb in dendritic cores was disclosed.